2012
DOI: 10.1002/pssc.201200314
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of excitons and biexcitons in (C4H9NH3)2PbBr4 crystals under high excitation density

Abstract: Optical properties in (C4H9NH3)2PbBr4 single crystals under high density excitation have been investigated by photoluminescence (PL) spectroscopy. The PL bands associated with the Γ1, Γ2 and Γ5 excitons and the biexcitons have been observed. While the Γ2 exciton and biexciton PL intensities are proportional to the 0.9 and 1.7 power of the excitation density, respectively, the Γ5 exciton PL intensity shows the nonlinear dependence on the excitation density. The excitation‐density dependence of the PL bands is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…As a consequence of the dielectric and quantum confinement effect, they show strongly bound and stable excitons at room temperature. [19,20] It has been experimentally observed that excitons are tightly confined in the inorganic layers with binding energy as high as a few hundred millielectronvolts (significantly higher than that of 3D perovskites). A comparison of bulk and surface exciton lifetimes yields a room temperature surface recombination velocity of 2 × 10 3 cm s −1 and an intrinsic lifetime of 185 ns.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…As a consequence of the dielectric and quantum confinement effect, they show strongly bound and stable excitons at room temperature. [19,20] It has been experimentally observed that excitons are tightly confined in the inorganic layers with binding energy as high as a few hundred millielectronvolts (significantly higher than that of 3D perovskites). A comparison of bulk and surface exciton lifetimes yields a room temperature surface recombination velocity of 2 × 10 3 cm s −1 and an intrinsic lifetime of 185 ns.…”
mentioning
confidence: 99%
“…Biexciton emission is evidenced at room temperature, with a binding energy of ≈45 meV and a lifetime of 80 ps. [20,23,24] The presence of these quasiparticles is exciting due to their unique role, leading to a better understanding of many body effects and their great promise for photonic applications. Transient photoluminescence resolves the low-lying dark exciton state, with a bright/dark splitting energy estimated to be 10 meV.…”
mentioning
confidence: 99%
See 3 more Smart Citations